SYMBOLIC FORM AND MEANING OF NONVERBAL ARTIFACTS OF DAWANESE COMMUNITY IN SOUTH CENTRAL TIMOR DISTRICT - Alex Djawa; Simon S. Ola; Jeladu Kosmas; Sebastianus Fernandez; Yoseph B. Kroon (Academic Journal of Educational Sciences, 2021)
The Dawan ethnic group is one of the ethnic groups who inhabit the island of Timor. This ethnic has artifacts as a hereditary heritage in this society. This artifact is in the form of nonverbal that has a symbolic form and meaning. The symbolic form and meaning of these artifacts can be understood conventionally and must be studied. The process of studying the form and symbolic meaning of this artifact, provides an overview of the ideology, behavior, values ​​and habits of the Dawan community. By knowing the forms and meanings of nonverbal artefacts in the Dawan community, it is possible to know the ideology, behavior, values ​​and habits that exist in this society.